2012
DOI: 10.1002/dvdy.23812
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic expression of Tbx1 protects the embryo from developmental defects caused by increased receptor tyrosine kinase signaling

Abstract: Background 22q11.2 deletion syndrome (22q11DS) is the most common microdeletion syndrome in humans, characterised by cardiovascular defects such as interrupted aortic arch, outflow tract defects, thymus and parathyroid hypo- or aplasia and cleft palate. Heterozygosity of Tbx1, the mouse homologue of the candidate TBX1 gene, results in mild defects dependent on genetic background, whereas complete inactivation results in severe malformations in multiple tissues. Results The loss of function mutations in two S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…E). This observation is in contrast to the severely reduced Spry1 and Spry2 expression in the pharyngeal region of Tbx1−/− embryos (Simrick et al, ). Taken together, these observations indicate that the near complete loss of Fgf8 expression in the endoderm of Tbx1cko embryos is not sufficient to cause an overall reduction in FGF signaling levels in the developing pharyngeal region at the time of caudal pouch formation.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…E). This observation is in contrast to the severely reduced Spry1 and Spry2 expression in the pharyngeal region of Tbx1−/− embryos (Simrick et al, ). Taken together, these observations indicate that the near complete loss of Fgf8 expression in the endoderm of Tbx1cko embryos is not sufficient to cause an overall reduction in FGF signaling levels in the developing pharyngeal region at the time of caudal pouch formation.…”
Section: Resultsmentioning
confidence: 70%
“…Although previous studies have shown that the expression of several genes encoding FGF ligands are altered in Tbx1 ‐deficient embryos, few reports describe the effect these changes have on downstream FGF signaling (Vitelli et al, ; Simrick et al, ). Therefore, to determine whether the reduced expression of Fgf8 in the endoderm affected FGF signaling in the Tbx1cko pharyngeal apparatus, we analysed the expression of two transcriptional read‐outs of FGF signaling, Etv4 and Etv5 (Klein et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haploinsufficiency of TBX1 is responsible for most of the symptoms of the DiGeorge/velo-cardio-facial syndrome, the most common microdeletion syndrome in humans 65 , 66 . Symptoms include congenital heart and craniofacial abnormalities, skeletal muscle hypotonia, and increased risk of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Because they overlap a predicted region of enhancer activity in HMEC, one of the functions of this hypermethylation may be to prevent the formation of an interfering heterologous enhancer in myogenic cells (Figure 3C). TBX1 haploinsufficiency has been linked to most of the symptoms of the DiGeorge 22q11.2 deletion syndrome [75]. Therefore, DMRs may be needed for precise regulation of this cell type-specific and development stage-specific gene.…”
Section: A Model For Multiple Functions Of Differentiation-linked Intmentioning
confidence: 99%